2022
DOI: 10.3390/ijms23020888
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic Acid/Eu(III) Complexes: Solution Equilibrium Studies, Structure Characterization and Biological Activity

Abstract: Caffeic acid (CFA) is one of the various natural antioxidants and chemoprotective agents occurring in the human diet. In addition, its metal complexes play fundamental roles in biological systems. Nevertheless, research on the properties of CFA with lanthanide metals is very scarce, and little to no chemical or biological information is known about these particular systems. Most of their properties, including their biological activity and environmental impact, strictly depend on their structure, stability, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 79 publications
(121 reference statements)
3
21
0
Order By: Relevance
“…The free ligand only elicited significant inhibition at 200 μM (32 %) (Figure 4). These results agreed with the results of Leung et al., who reported that, compared to free ligands, their metal complexes frequently hold superior lipophilicity profiles, which allow them to cross cell membranes more easily, to exert their biological effects [70,71] . Surprisingly, 2 did not inhibit mast cell degranulation (Figure SI 11), probably because of the lower lipophilicity of the phenanthroline ligand when compared to 1 , which bears a methyl substituent in its phen ligand.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The free ligand only elicited significant inhibition at 200 μM (32 %) (Figure 4). These results agreed with the results of Leung et al., who reported that, compared to free ligands, their metal complexes frequently hold superior lipophilicity profiles, which allow them to cross cell membranes more easily, to exert their biological effects [70,71] . Surprisingly, 2 did not inhibit mast cell degranulation (Figure SI 11), probably because of the lower lipophilicity of the phenanthroline ligand when compared to 1 , which bears a methyl substituent in its phen ligand.…”
Section: Resultssupporting
confidence: 90%
“…These results agreed with the results of Leung et al, who reported that, compared to free ligands, their metal complexes frequently hold superior lipophilicity profiles, which allow them to cross cell membranes more easily, to exert their biological effects. [70,71] Surprisingly, 2 did not inhibit mast cell degranulation (Figure SI 11), probably because of the lower lipophilicity of the phenanthroline ligand when compared to 1, which bears a methyl substituent in its phen ligand. To prevent false positive results concerning inhibition of mast cell degranulation, we investigated whether the action of 1 was due to inhibition of the enzymatic activity or β-hexosaminidase release.…”
Section: Biological Assaysmentioning
confidence: 99%
“…15 However, it is common for herbal medicines to be prepared as a decoction in water, during which many organic components containing ligand groups (e.g., hydroxyl, carboxyl, carbonyl, amino, o-diphenol hydroxyl) may form complexes with metal ions, increasing their pharmacological activities or even forming new agents. For example, quercetin-Ca, 16 curcumin-Cu, 17,18 and curcumin-Fe 19 are better than their respective ligands at free radical scavenging; emodin-Cu, 20 apigenin-V, 21 and baicalin-Ce/La/Y 22 have better antitumor activity; tea polyphenols-Zn, 23 curcumin-Mn, 24 and caffeic acid-Eu 25 have significantly increased antibacterial activity against Gram-positive and Gram-negative bacteria. Therefore, metal complexes may be the active components of aqueous extracts used in traditional Chinese medicine, creating a new base for the discovery of antibacterial drug candidates.…”
Section: Introductionmentioning
confidence: 99%
“…Organic substances are crucial for the potential phenomena of adsorption or chelation, which may influence the impact of these metals on organisms and microorganisms sharing the same ecological niche. Thus, the last decade has seen an increasing interest among the scientific community for the coordination properties of organic ligands toward rare-earth elements [ 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%